The Effectiveness of Stress Coping Skills Training on Mindfulness of Female students - Haddadi , Katayon; Abed , Nazanin (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to determine the effectiveness of Stress Coping Skills Training on Mindfulness of Female students.Methodology: This quasi-experimental study was carried out in a pre-test and post-test design with control group. Sixty-nine students were selected from among the girls of the 9th grade in Tehran during the academic year of 2017-18 and were randomly assigned to experimental and control groups. The Mindfulness Questionnaire (Baer & et al., 2006) was performed in the pre-test phase and after training the skills of confronting stress with the experimental group, the questionnaire was repeated on both groups. Data analysis was done by SPSS19 software in two parts: descriptive and inferential (covariance). Findings: The results showed that by controlling the effect of pre-test, the mind-consciousness scores of the experimental group significantly increased in the post-test phase. The results show that the teaching of skills to confront mind-tone stress increases students' awareness. Learning these skills will increase the decentralization and dare of students' exposure to stressful thoughts, which leads to higher awareness. Also, stress coping skills lead to cognitive reform and the ability to manage themselves, and subsequently their minds increase.Conclusion: Therefore, it can be said that teaching strategies for coping with stressful situations are an effective way to increase students' mindfulness.